METODE PENERJEMAHAN NON – EQUIVALENT WORD LEVEL STUDI KASUS MENTERJEMAHKAN NOVEL PRINCESS DIARIES KARYA MEG CABOT - Yulianti Yulianti; Dendi Suhendi; Feny Putri Maharany (Jurnal Soshum Insentif, 2021)
Abstract - The purpose of the study is to know The Strategy in Translating Non-Equivalent Word Levels in the Novel of “The Princess Diaries”, written by Meg Cabot. Sample of the research is taken from both English and Indonesian Novel version. The research methodology that is used Descriptive Qualitative Method and the technique of data analysis that is used is a descriptive-documentation method. The researches finding are: 1). There are some translation strategies dealing with problems of non-equivalent word level by Mona Baker are used in translating the novel; Translation by using a loan word or loan word plus explanation is used 61 times, translation by paraphrase using a related word is used 22 times, translation by paraphrase using unrelated word is used 25 times, translation by omission is used 7 times, and translation by cultural substitution is used 13 times. 2). There is the dominant type in translating the novel of The Princess Diaries, and The loan word or loan word plus explanations is the dominant type in translating the novel. It has the highest data about 47, 66%. These strategies are also used in to make the result of translation not only enjoyable but also meaningful for the readers. Abstrak - Tujuan penelitian ini adalah untuk mengetahui strategi penerjemahan pada tingkatan kata yang tidak ada padanannya dalam novel “The Princess Diaries” karya Meg Cabot. Sample yang digunakan dalam penelitian ini adalah sebuah novel dengan menggunakan kedua versi baik Indonesia maupun Inggris. Metode yang digunakan adalah deskriptif kualitatif dan menggunakan teknik dokumentasi deskriptif. Terdapat dua hal dalam penelitian ini, yaitu: 1. Terdapatnya lima strategi penerjemahan pada tingkatan kata yg tidak ada padanannya dalam novel “The Princess Diaries” dengan merujuk kepada teori Mona Baker; Strategi dengan menggunakan kata pinjaman, Strategi dengan menggunakan prasa yang berhubungan, Strategi dengan menggunakan prasa yang tidak berhubungan, Strategi yang menggunakan penghilangan kata, dan Startegi yang menggunakan subtitusi budaya. 2. Terdapatnya strategi yang paling dominan digunakan oleh pengarang dalam novel “The Princess Diaries” yakni strategi menggunakan kata pinjaman, terdapat 61 data atau sebanyak 47,66 % berupa kata maupun prasa. Diharapkan startegi yang digunakan dalam penelitian ini mampu menghasilkan penerjemahan yang bermakna dan mudah dipahami pembaca.